2021
DOI: 10.1002/cjp2.204
|View full text |Cite
|
Sign up to set email alerts
|

The presence of tumour‐infiltrating neutrophils is an independent adverse prognostic feature in clear cell renal cell carcinoma

Abstract: Tumour-promoting inflammation is an emerging hallmark of cancer that is increasingly recognised as a therapeutic target. As a constituent measure of inflammation, tumour-infiltrating neutrophils (TINs) have been associated with inferior prognosis in several cancers. We analysed clinically annotated cohorts of clear cell renal cell carcinoma (ccRCC) to assess the presence of neutrophils within the tumour microenvironment as a function of outcome. We centrally reviewed ccRCC surgical resection and fine-needle as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…For example, Braun et al found a higher proportion Disease Markers of exhausted CD8 + T cells and immunosuppressive M2-like macrophages in patients with advanced ccRCC, and this inhibitory effect showed progressive immune dysfunction as the disease stage of ccRCC progressed [36]. Tessier-Cloutier et al found that ccRCC microenvironment is infiltrated with a large number of neutrophils, many of which act directly on tumor tissue by releasing elastase thereby promoting tumor spread [37]. The consequences indicate therapy against microenvironmental immunity cellulas can be an efficient strategy for delaying disease progression and activating immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Braun et al found a higher proportion Disease Markers of exhausted CD8 + T cells and immunosuppressive M2-like macrophages in patients with advanced ccRCC, and this inhibitory effect showed progressive immune dysfunction as the disease stage of ccRCC progressed [36]. Tessier-Cloutier et al found that ccRCC microenvironment is infiltrated with a large number of neutrophils, many of which act directly on tumor tissue by releasing elastase thereby promoting tumor spread [37]. The consequences indicate therapy against microenvironmental immunity cellulas can be an efficient strategy for delaying disease progression and activating immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Castle et al [21] reported that dendritic cells activate T cells in patients and increase cytotoxic T cell production, exerting anti-tumor effects. Basile et al [22] demonstrated that high tumor-infiltrating neutrophils were linked to poor overall survival in ccRCC patients. A previous study found that in patients with ccRCC mast cells [23] and high infiltration, the immune treatment may be effective with an improved prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid dendritic cells generated chemokine ligand 17 that recruited T cells as well as other activated antigen-presenting cells and was an independent prognostic factor for OS in ccRCC patients [ 25 ]. Tumor-infiltrating neutrophils were involved in the prognostic deterioration of ccRCC by releasing elastase that broke down cell-cell adhesion and promoted tumor propagation [ 26 ]. Interferon receptors, cytokine receptors and interleukins could impair the prognosis of ccRCC through reconfiguring the immune landscape of TME [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%